Interpreter's Contribution in Conference Interpreting and Indonesia Education - Suryadi, Fidela Shaumi; Mubaroq, Fadel Muhamad; Saehu, Andang (Program Studi Pendidikan Bahasa Inggris, 2024)
The aim of this study is to report the interpreter’s contribution in conference interpreting and explore their contributions to the Indonesia's education. The grand theory used in this research is theory of interpreter's contribution proposed by Souza (2017). Qualitative research was utilized to collect and analyze data, employing open-ended interviews with professional interpreter as participant. The study found that interpreters play an important contribution in bridging communication gaps and ensuring effective communication in diverse educational settings such as importance of experience, technique, and overall skills in determining an interpreter's contribution. Additionally, the overall skills of an interpreter, including their cultural competence, adaptability, and ability to handle stress, are crucial to ensuring successful communication in educational contexts. By leveraging it, interpreters significantly contribute to the educational environment, promoting inclusivity and mutual understanding.